Exogenous Glutathione Completes the Defense against Oxidative Stress in Haemophilus influenzae - Vergauwen, Bjorn (American Society for Microbiology, 2003)
Since they are equipped with several strategies by which they evade the antimicrobial defense of host macrophages, it is surprising that members of the genus Haemophilus appear to be deficient in common antioxidant systems that are well established to protect prokaryotes against oxidative stress. Among others, no genetic evidence for glutathione (γ-Glu-Cys-Gly) (GSH) biosynthesis or for alkyl hydroperoxide reduction (e.g., the Ahp system characteristic or enteric bacteria) is apparent from the Haemophilus influenzae Rd genome sequence, suggesting that the organism relies on alternative systems to maintain redox homeostasis or to reduce small alkyl hydroperoxides. In this report we address this apparent paradox for the nontypeable H. influenzae type strain NCTC 8143. Instead of biosynthesis, we could show that this strain acquires GSH by importing the thiol tripeptide from the growth medium. Although such GSH accumulation had no effect on growth rates, the presence of cellular GSH protected against methylglyoxal, tert-butyl hydroperoxide (t-BuOOH), and S-nitrosoglutathione toxicity and regulated the activity of certain antioxidant enzymes. H. influenzae NCTC 8143 extracts were shown to contain GSH-dependent peroxidase activity with t-BuOOH as the peroxide substrate. The GSH-mediated protection against t-BuOOH stress is most probably catalyzed by the product of open reading frame HI0572 (Prx/Grx), which we isolated from a genomic DNA fragment that confers wild-type resistance to t-BuOOH toxicity in the Ahp-negative Escherichia coli strain TA4315 and that introduces GSH-dependent alkyl hydroperoxide reductase activity into naturally GSH peroxidase-negative E. coli. Finally, we demonstrated that cysteine is an essential amino acid for growth and that cystine, GSH, glutathione amide, and cysteinylglycine can be catabolized in order to complement cysteine deficiency.